2016
DOI: 10.1002/path.4730
|View full text |Cite
|
Sign up to set email alerts
|

RecurrentMALAT1-GLI1oncogenic fusion andGLI1up-regulation define a subset of plexiform fibromyxoma

Abstract: Plexiform fibromyxomas are rare neoplasms, being officially recognized as a distinct entity among benign mesenchymal gastric tumors in the 2010 WHO Classification of Tumors of the Digestive System. Characteristically, these tumors have a multinodular/plexiform growth pattern, and histologically contain variably cellular areas of bland myofibroblastic type spindle cells embedded in an abundant myxoid matrix, rich in capillary-type vessels. As of yet, the molecular and/or genetic features of these tumors are unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
104
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 20 publications
1
104
1
3
Order By: Relevance
“…3 A recent study also mentioned that the gene glioma-associated oncogene homologue 1 (GLI1) may be present in a subgroup of these tumors. 10 In our series, we had an unusual consultation case that has nuclear pleomorphism, increased mitotic activity with three mitotic figures in 10 highpower field with six PHH3 positive cells in 5 mm 2 area, and 30% of Ki-67 proliferation index as well as a synchronous 0.7 cm GIST. This tumor did not show lymphovascular invasion or perineural invasion.…”
Section: Discussionmentioning
confidence: 85%
“…3 A recent study also mentioned that the gene glioma-associated oncogene homologue 1 (GLI1) may be present in a subgroup of these tumors. 10 In our series, we had an unusual consultation case that has nuclear pleomorphism, increased mitotic activity with three mitotic figures in 10 highpower field with six PHH3 positive cells in 5 mm 2 area, and 30% of Ki-67 proliferation index as well as a synchronous 0.7 cm GIST. This tumor did not show lymphovascular invasion or perineural invasion.…”
Section: Discussionmentioning
confidence: 85%
“…Breakpoint positions are indicated by arrows. Recently, the MALAT1-GLI1 fusion gene was reported in a subset of plexiform fibromyxomas, in gastroblastomas, and in epithelioid tumors with metastatic potential (5,34,35). The MALAT1 gene (on 11q13.1) is ubiquitously expressed and produces a long non-coding RNA (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…The MALAT1 gene (on 11q13.1) is ubiquitously expressed and produces a long non-coding RNA (36,37). Part of MALAT1 was fused to exon 6 (plexiform fibromyxomas) or to the last 19 nt of the 145 bp long exon 5 (gastroblastoma) of GLI1 (34,35). Spans et al (34) showed that the truncated GLI1 protein (lacking exons 1-5) was transcriptionally active.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MALAT1 is dysregulated and plays a critical role in the development and progression of various cancer types (34)(35)(36)(37). A recurrent MALAT1-GLI1 fusion, resulting in GLI family zinc finger 1 (GLI1) overexpression, was described in gastroblastomas and plexiform fibromyxomas (38,39).…”
Section: Discussionmentioning
confidence: 99%